Australia's awareness of cardiac arrest and rates of CPR training: results from the Heart Foundation's HeartWatch survey. Issue 1 (6th January 2020) - Cartledge, Susie; Saxton, Danielle; Finn, Judith; Bray, Janet E
Abstract : Objective: We aimed to provide the first national estimates of cardiopulmonary resuscitation (CPR) training and awareness of cardiac arrest. Design: A retrospective analysis of a national cross-sectional survey was undertaken. Data were collected online from adults in July 2017 as part of the Heart Foundation of Australia's HeartWatch survey. We used logistic regression to examine demographic factors associated with CPR training. Participants: A national cohort was invited to participate in the survey using purposive, non-probability sampling methods with quotas for age, gender and area of residence, in order to reflect the wider Australian population. The final sample consisted of 1076 respondents. Main outcome measure: To determine an estimation of the prevalence of cardiac arrest awareness and CPR training at a national level and the relationship of training to demographic factors. Results: The majority (76%) of respondents were born in Australia with 51% female and 66% aged between 35 and 64 years. Only 16% of respondents could identify the difference between a cardiac arrest and a heart attack. While 56% reported previous CPR training, only 22% were currently trained (within 1 year). CPR training was associated with younger age (35 to 54 years) (OR 1.45, 95% CI 1.06 to 2.0), being born in Australia (OR 1.59, 95% CI 1.17 to 2.17) and higher levels of education (university, OR 1.86, 95% CI 1.35 to 2.57). CPR training increased confidence in respondents ability to perform effective CPR and use a defibrillator. Lack of CPR training was the most common reason why respondents would not provide CPR to a stranger. Conclusions: There is a need to improve the community's understanding of cardiac arrest, and to increase awareness and training in CPR. CPR training rates have not changed over the past decades—new initiatives are needed.